miRNAs in ancient tissue specimens of the Tyrolean iceman - Keller, Andreas; Kreis, Stephanie; Meder, Benjamin (Molecular biology and evolution, 2017)
Abstract. The analysis of nucleic acids in ancient samples is largely limited to DNA. Small noncoding RNAs (microRNAs) are known to be evolutionary conserved a